LAW REFORM OF THE INDONESIA’S SOCIAL HEALTH INSURANCE FOR THE POST COVID-19 PANDEMIC (A DIGNIFIED JUSTICE PERSPECTIVE) - Teguh Prasetyo; Jeferson Kameo; Tri Astuti Handayani (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
There have been an existing problem in Indonesia. We have been told that Indonesia’s social security system, particularly its national health social insurance (JKN) is not equipped to deal with the health and economic shocks associated with a pandemic such as Covid-19. In this article we look at how Indonesia must prepare to face a possible chalanges, post Covid-19 Pandemic. We argue that the government need to focus on a clear legal strategy to address the medium-and longer-term implications of a pandemic such as Covid-19. Since the pandemic has ended, appart from technicals efforts such as continuing reducing the rate endemic of infection through effective testing and tracing and enforcing social distancing and mobility restrictions, the government need to reform the JKN in order to be able to support all the populations particularly the poor and near-poor. A legal philosophy for the reform scheme is needed to reducing long-term poverty and preventing structural changes in unemployment that undermining the JKN. As a report of a legal research, this paper used normative methodology to examine primary legal material such as legislations pertaining to the JKN. It has been found that the Covid-19 pandemic undermines the JKN in the form of legislations regulating this particular field, and it is needed to be reformed.Keywords: Indonesia, Social Health Insurance, Dignified Justice Jurisprudence.